Topographic Map of the Moon's South Pole (80°S to Pole) - Stopar, Julie; orcid:0000-0003-1578-3688; Meyer, Heather M.; orcid:0000-0002-6888-9868 (Lunar and Planetary Institute, Regional Planetary Image Facility, 2019)
This map is based on data released by the Lunar Reconnaissance Orbiter Lunar Orbiter Laser Altimeter (LOLA). The map is centered on the south pole and shows the LOLA 20-m elevation product between 80°S and the pole (NASA Goddard Space Flight Center; Smith et al., 2010; Smith et al., 2017). The elevation data are overlain on a derived hillshade with solar azimuth 45°W and solar elevation 45°. Polar stereographic projection is used with scale true at the pole. Feature names are included on the map.